2014
DOI: 10.1159/000357238
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Type-Specific Expression of Low-Density Lipoprotein Receptor-Related Protein 6 in Human Skeletal Muscles

Abstract: Objective: Gene expression patterns differ in the two types of skeletal muscle fiber. The Wnt signaling pathway, which includes low-density lipoprotein receptor-related protein 6 (LRP6), has been associated with cell differentiation and glucose metabolism in skeletal muscles. We examined the relationships between muscle fiber types and LRP6 expression. Methods: Adenosine triphosphatase was assayed histochemically, and the levels of expression of LRP6 and myosin were analyzed immunohistochemically, in frozen se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Activation of Wnt‐YAP signaling following increased (P)RR is tightly involved in the induction of skeletal muscle atrophy, but it remains unclear how (P)RR activates Wnt‐YAP signaling selectively in fast muscle. The Wnt receptor LRP6, a binding partner of (P)RR, has been reported to be predominantly expressed in fast muscle (Takeda et al, ). The expression pattern of LRP6 may contribute to fast muscle‐specific activation of the Wnt pathway in (P)RR‐Tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of Wnt‐YAP signaling following increased (P)RR is tightly involved in the induction of skeletal muscle atrophy, but it remains unclear how (P)RR activates Wnt‐YAP signaling selectively in fast muscle. The Wnt receptor LRP6, a binding partner of (P)RR, has been reported to be predominantly expressed in fast muscle (Takeda et al, ). The expression pattern of LRP6 may contribute to fast muscle‐specific activation of the Wnt pathway in (P)RR‐Tg mice.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the Wnt/β-catenin signaling pathway is anabolic in skeletal muscle [ 32 ] and sclerostin co-incubation has been shown to abolish Wnt3a-mediated C2C12 differentiation in culture, demonstrating that sclerostin antagonizes Wnt-signaling in an isolated murine muscle cell line [ 13 ]. However, LRP6 expression is fiber-type specific, with normal and atrophic human skeletal muscle expressing LRP6 only in type II fibers and C2C12 cells expressing LRP6 only in the presence of fast myosin [ 12 ], explaining the relatively low LRP6 mRNA expression that we observed in the soleus, a muscle comprised predominantly of type I fibers. In comparison, Tran et al reported >50% of cultured myoblasts from murine muscle were LRP5 positive, although, satellite cells for this experiment were isolated from the tibialis anterior [ 32 ], which is composed of predominantly type II fibers.…”
Section: Discussionmentioning
confidence: 99%
“…Sclerostin influences SCI-induced bone loss, as evidenced by (1) increased sclerostin mRNA expression in bone acutely after SCI [ 7 ], (2) mice with sclerostin gene deletion that do not exhibit bone loss after spinal cord transection [ 9 ], and (3) the ability pharmacologic sclerostin-inhibition to completely prevent cancellous bone loss in rats following SCI [ 2 , 10 ]. Others have suggested that sclerostin may also influence skeletal muscle [ 5 ], a supposition that is strengthened by the understanding that sclerostin is present in the circulation [ 8 ], that LRP5/LRP6 are expressed in human muscle [ 11 , 12 ], and that the Wnt/β-catenin signaling pathway is anabolic in muscle [ 3 ]. Interestingly, Huang et al recently reported that Wnt3a, an osteocyte-derived Wnt-signaling agonist, promoted C2C12 cell differentiation in vitro and that sclerostin co-incubation (100 ng/ml) prevented this effect [ 13 ], demonstrating that sclerostin negatively regulates Wnt-signaling in a mouse skeletal muscle cell line, at least when present in relatively high concentrations.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that sclerostin is not solely produced by osteocytes and does not just effect bone; rather, other cell types are increasingly being found to be affected by sclerostin through the systemic circulation ( Battaglino et al, 2012 ). For example, there is increasing evidence of sclerostin’s effects on skeletal muscle, which is strengthened by the fact that LRP5/LRP6 are expressed in human muscle and that the Wnt/β-catenin signaling pathway is anabolic in muscle ( Tagliaferri et al, 2015 ; Karczewska-Kupczewska et al, 2016 ; Takeda et al, 2014 ; Rudnicki and Williams, 2015 ). Interestingly, Huang and colleagues recently reported that Wnt3a, an osteocyte-derived Wnt-signaling agonist, promoted C2C12 cell differentiation in vitro and that sclerostin co-incubation (100 ng/ml) prevented this effect, demonstrating that sclerostin negatively regulates Wnt-signaling in a mouse skeletal muscle cell line, at least when present in relatively high concentrations ( Huang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%